2011
DOI: 10.1364/oe.19.002476
|View full text |Cite
|
Sign up to set email alerts
|

Polarization switching and polarization mode hopping in quantum dot vertical-cavity surface-emitting lasers

Abstract: We show experimentally that polarization mode hopping in quantum dot vertical cavity surface emitting lasers (VCSELs) takes place between nonorthogonal elliptically polarized modes. In contrast to quantum well VCSELs the average dwell time decreases with injection current. This decrease is by 8 orders of magnitude: from seconds to nanoseconds and is achieved without any modifications of the VCSEL internal anisotropies. The observed scaling happens in a range of currents as wide as 8 times the threshold value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 17 publications
7
35
0
Order By: Relevance
“…3-(b). These two statistical features agree qualitatively well with what is seen in our experiment 33 . It is worth mentioning that the exponentially decaying statistical distribution of the dwell time is the result of polarization nonlinear deterministic dynamics and, in contrast to all previous studies, is not the result of a noise-driven Kramers hopping problem.…”
Section: Statistics Of the Deterministic Mode Hoppingsupporting
confidence: 92%
See 3 more Smart Citations
“…3-(b). These two statistical features agree qualitatively well with what is seen in our experiment 33 . It is worth mentioning that the exponentially decaying statistical distribution of the dwell time is the result of polarization nonlinear deterministic dynamics and, in contrast to all previous studies, is not the result of a noise-driven Kramers hopping problem.…”
Section: Statistics Of the Deterministic Mode Hoppingsupporting
confidence: 92%
“…Our main contribution is the analysis of experimental data. Measurements of the data are already described elsewhere 33 and we will therefore focus on the method to reduce the noise in our dataset. Here we use a re-embedding procedure based on singular value analysis as described by Fraedrich 42 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The polarization instability that mainly comes from the competition between two orthogonally polarized states generally occurs in small-area VCSELs [11]- [14]. It has been recently observed that the spatial morphologies of high-order transverse modes in broad-area VCSELs are strongly related to the directions of their polarization states [15], [16].…”
Section: Introductionmentioning
confidence: 99%